HEDON, the Household Energy Network - Harvey, Blane; Ensor, Jonathan; Carlile, Liz; Garside, Ben; Patterson, Zachary; Naess, Lars Otto (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
A website that informs and empowers practices on household energy, by addressing knowledge gaps, facilitating partnerships and fostering information sharing. The website tries to be a place where practitioners, policy-makers, funders, and business-owners actively pursue a cleaner, affordable and more efficient household energy sector. They share their experiences, learn from one another, and create new knowledge. The HEDON web-portal has discussion forums, wiki-pages on household related energy services (focused on renewable energy), as well as a single repository for blogs, resources, data on renewable projects, and a collection of contact members.